Семантика природных стихий в „Школе для дураков” Саши Соколова - Żejmo, Bożena (Studia Rossica Posnaniensia, 2019)
The objective of this article is to analyse two classical elements: the air (the wind) and the earth in Sasha Sokolov’s novel A School for Fools. The antithesis of the elements creates a symbolic space in a text, which the author interprets as a confrontation of freedom (the air) with the Soviet enslavement system (the earth). In this fight, it is the wind that exhibits more power as a destructive force, bringing an eschatological sense to the text.